Snow White with the red hair. 5 - Akiduki, Sorata (Shojo beat manga., 2020)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! The prince from the neighboring kingdom, Zen, rescues her from her plight, and thus begins their love story ... When a banquet invitation arrives from Prince Raj in Tanbarun, Izana tests Zen and Shirayuki's budding relationship by forcing Shirayuki to accept. But before the young lovers can cope with their impending time apart, a new threat arrives in Clarines--and he's got Shirayuki in his sights!